Ras-Dependent Regulation of c-Jun Phosphorylation Is Mediated by the Ral Guanine Nucleotide Exchange Factor-Ral Pathway - de Ruiter, Nancy D. (American Society for Microbiology, 2000)
The transcription factor c-Jun is critically involved in the regulation of proliferation and differentiation as well as cellular transformation induced by oncogenic Ras. The signal transduction pathways that couple Ras activation to c-Jun phosphorylation are still partially elusive. Here we show that an activated version of the Ras effector Rlf, a guanine nucleotide exchange factor (GEF) of the small GTPase Ral, can induce the phosphorylation of serines 63 and 73 of c-Jun. In addition, we show that growth factor-induced, Ras-mediated phosphorylation of c-Jun is abolished by inhibitory mutants of the RalGEF-Ral pathway. These results suggest that the RalGEF-Ral pathway plays a major role in Ras-dependent c-Jun phosphorylation. Ral-dependent regulation of c-Jun phosphorylation includes JNK, a still elusive JNKK, and possibly Src.